Hot-dip galvanized steel

The molten plated steel material with a tailored plating layer composition and Si intermetallic compounds addresses the issues of plating layer degradation, hardness, and workability in conventional Zn-Al-Mg plated steels, achieving enhanced corrosion resistance and workability.

JP7653049B1Active Publication Date: 2025-03-28NIPPON STEEL CORPORATION
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2024566728
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2023-08-01
Filing Date
2024-08-01
Publication Date
2025-03-28
Estimated Expiration
2044-08-01

AI Technical Summary

Technical Problem

Conventional Zn-Al-Mg plated steel materials face issues such as degradation of the plating layer, insufficient hardness, and unstable scratch resistance due to the form of intermetallic compounds and their distribution in the plating layer.

Method used

A molten plated steel material with a plating layer composition of Al: 10.0-60.0%, Mg: 4.0-15.0%, Si: 3.5-8.0%, and additional elements within specific ranges, which includes Si intermetallic compounds to enhance hardness and corrosion resistance while improving workability.

Benefits of technology

The solution achieves sufficient plating hardness, excellent workability, and excellent corrosion resistance, addressing the limitations of conventional materials by optimizing the intermetallic compound distribution and composition.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007653049000005
    Figure 0007653049000005
  • Figure 0007653049000006
    Figure 0007653049000006
  • Figure 0007653049000001
    Figure 0007653049000001
Patent Text Reader

Abstract

This hot-dip plated steel material has a coating layer having a chemical composition containing, in mass%, Al: more than 10.0% but not more than 60.0%, Mg: 4.0 to 15.0%, Si: 3.5% to 8.0%, and the balance Zn and impurities, and in an element distribution profile obtained by qualitatively analyzing the coating layer surface toward the steel material by the GDS method, when the thickness of the region from the coating layer surface to the depth position where an Fe intensity equivalent to 5% of the maximum Fe intensity is detected is Tg, the average value of Si from the coating layer surface to Tg / 3 is Si(surf), the average value of Si in the range from Tg / 3 to 2Tg / 3 starting from the coating layer surface is Si(centre), and the average value of Si in the range from 2Tg / 3 to Tg starting from the coating layer surface is Si(deep), the following formula (1) is satisfied. Si(surf) <Si(deep)<Si(centre) …(1)
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a hot-dip galvanized steel material. This application claims priority based on Japanese Patent Application No. 2023-125776, filed on August 1, 2023, the contents of which are incorporated herein by reference. [Background technology]

[0002] When steel materials are used for a long period of time, it is preferable to apply some kind of rust-proofing treatment to the steel materials to make them resistant to corrosion. Hot-dip galvanizing is used as a cheap method of rust-proofing steel materials in various fields where rust prevention is required, such as civil engineering, construction, and automotive fields.

[0003] The corrosion protection means by the plating layer is roughly determined by the inherent corrosion resistance of the plating layer and the thickness of the plating layer. For example, Patent Document 1 describes the production of a plated steel sheet by a so-called continuous hot-dip plating method in which a steel sheet is continuously immersed in a hot-dip plating bath. The plated steel sheet is then processed into a part shape to produce the part.

[0004] In recent years, various studies have been conducted to improve the performance of plated steel sheets.

[0005] For example, Patent Documents 1 and 2 disclose Zn-Al-Mg plated steel materials (steel sheets) as plated steel materials with high corrosion resistance. In these Zn-Al-Mg plated steel materials, the corrosion resistance and other performance properties are improved by controlling the structure of the plated layer, adding elements to the plated layer, or actively forming corrosion products. [Prior art documents] [Patent documents]

[0006] [Patent Document 1] International Publication No. 2018 / 139619 [Patent Document 2] International Publication No. 2019 / 230894 Summary of the Invention [Problem to be solved by the invention]

[0007] In conventional Zn-Al-Mg plated steel materials as described in Patent Documents 1 and 2, the morphology of intermetallic compounds in the plated layer has not been fully investigated, except for major ones. Therefore, under severe processing conditions, problems such as reduced workability, such as peeling (powdering) of the plated layer, may occur due to the intermetallic compounds. Furthermore, in conventional Zn-Al-Mg plated steel materials, the hardness of the plated layer is insufficient, and it may be difficult to stably ensure good scratch resistance.

[0008] An object of one embodiment of the present invention is to provide a hot-dip plated steel material that is capable of achieving sufficient plating hardness, excellent workability, and excellent corrosion resistance all at the same time. [Means for solving the problem]

[0009] In order to solve the above problems, each aspect of the present invention employs the following configuration. [1] A hot-dip plated steel material according to one embodiment of the present invention has a steel material and a plating layer disposed on a surface of the steel material, The plating layer comprises, in mass %, Al: more than 10.0%, less than 60.0%, Mg: 4.0% or more, 15.0% or less, Si: 3.5% or more, 8.0% or less, and further comprising Sn: 0% or more, 0.7% or less, Sr: 0% or more, 1.5% or less, Bi: 0% or more, 0.3% or less, In: 0% or more, 0.3% or less, Ca: 0% or more, 0.6% or less, Y: 0% or more, 0.3% or less, La: 0% or more, 0.3% or less, Ce: 0% or more, 0.3% or less, Li: 0% or more, 0.3% or less, Ni: 0% or more, 1.0% or less, Cu: 0% or more, 1.0% or less, Ag: 0% or more, 0.25% or less, Sb: 0% or more, 0.25% or less, Pb: 0% or more, 0.25% or less, B: 0% or more, 0.5% or less, P: 0% or more, 0.5% or less, Ti: 0% or more, 0.25% or less, Co: 0% or more, 0.25% or less, V: 0% or more, 0.25% or less, Nb: 0% or more, 0.25% or less, Mn: 0% or more, 0.25% or less, Zr: 0% or more, 0.25% or less, W: 0% or more, 0.25% or less, Fe: 0% or more, 5.0% or less, The chemical composition includes the balance Zn and impurities. The plating layer contains an MgSi intermetallic compound, In an element distribution profile obtained by qualitatively analyzing the surface of the plating layer toward the steel material by glow discharge optical emission spectrometry, if the thickness of a region from the surface of the plating layer to a depth position at which an Fe intensity equivalent to 5% of the maximum Fe intensity is detected is Tg, the average value of the qualitative analysis value of Si from the surface of the plating layer to Tg / 3 is Si(surf), the average value of the qualitative analysis value of Si in the range from Tg / 3 to 2Tg / 3 starting from the surface of the plating layer is Si(centre), and the average value of the qualitative analysis value of Si in the range from 2Tg / 3 to Tg starting from the surface of the plating layer is Si(deep), the following formula (1) is satisfied. Si(surf) <Si(deep)<Si(centre) …(1) [2] In the hot-dip plated steel material described in [1] above, an X-ray diffraction pattern of the surface of the plating layer measured using Cu-Kα radiation at an X-ray output of 50 kV and 300 mA may satisfy the following formula (2): {I(26.19°)+I(44.6°)} / {2×I(12.5°)}>2.0 …(2) In equation (2), I(n°) is the X-ray diffraction intensity at a diffraction angle of n°, where n is the diffraction angle (2θ) shown in equation (2). Effect of the Invention

[0010] According to one embodiment of the present invention, it is possible to provide a hot-dip plated steel material that is capable of achieving sufficient plating hardness, excellent workability, and excellent corrosion resistance all at the same time. [Brief description of the drawings]

[0011] [Figure 1] FIG. 2 is a graph showing an example of an element distribution profile, showing the results of a GDS analysis performed on a coating layer of a hot-dip coated steel material according to an embodiment of the present invention. [Diagram 2] 3 shows an example of an X-ray diffraction pattern of a plating layer according to an embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0012] Hereinafter, a hot-dip plated steel material according to one embodiment of the present invention will be described. In this specification, the "%" designation for the content of each element in the chemical composition of the plating layer means "mass %" unless otherwise specified. Furthermore, a numerical range expressed using "~" means a range that includes the numerical values ​​before and after "~" as the lower and upper limits. When the numerical values ​​before and after "~" are followed by "more than" or "less than," the numerical range does not include these numerical values ​​as the lower or upper limit.

[0013] First, we investigated the relationship between the intermetallic compounds formed in the Zn-Al-Mg-based coating layer and the workability of the coated steel material. The results of this investigation are explained below.

[0014] In general, when a plating layer contains an intermetallic compound having a covalent bond, the particles become hard, increasing the hardness of the entire plating layer. In addition, since intermetallic compounds have excellent insulating properties, their inclusion in the plating layer provides high corrosion resistance.

[0015] On the other hand, if an excessive amount of intermetallic compounds is contained in the plating layer, the entire plating layer becomes hard, and the plastic deformability of the plating layer may decrease. In addition, if the entire plating layer becomes hard, the plating layer becomes easily broken when the plated steel material is used for forming processing, and peeling of the plating layer such as powdering may occur. Therefore, it is not practically preferable to contain a large amount of intermetallic compounds in the plating layer.

[0016] Furthermore, when intermetallic compounds are formed continuously and in a layer shape, particularly on the surface and interface of a plating layer, peeling may occur during bending, or interfacial peeling may occur at the interface between the plating layer and the base material due to a difference in corrosion rate during corrosion. Thus, there has been a demand for a plating layer that has a desired level of hardness and high corrosion resistance, and has good workability that does not cause peeling or the like.

[0017] Here, there is a technology to include Ca in the coating layer in order to improve the hardness and corrosion resistance of the coating layer. When a large amount of Ca is included in the coating layer, an intermetallic compound is formed with Zn, Al, etc. in the coating layer. The melting point of this Ca-containing intermetallic compound is very high in the solidification process of Zn-Al-Mg hot-dip coating. Therefore, the Ca in the coating layer becomes a large Ca-containing intermetallic compound in the early stage after the steel material is pulled out of the coating bath, and grows in the coating layer.

[0018] In a normal hot-dip plating process, the surface of the plating layer is largely cooled by the outside air, so the solidification of the plating layer proceeds from the surface. In a bath containing Ca, the same mechanism causes the precipitation of Ca-containing intermetallic compounds to start from the surface or interface of the plating layer, where the free energy is low and stable. As a result, Ca-containing intermetallic compounds tend to accumulate, especially on the surface of the plating layer, and may grow coarsely to form a layer of Ca-containing intermetallic compounds.

[0019] In the case of a plating layer in which Ca-containing intermetallic compounds are connected in layers, the Ca-containing intermetallic compounds may undergo brittle fracture during forming, causing the plating layer to peel off from the surface, a phenomenon known as "powdering." Therefore, it has been difficult to improve the hardness, workability, and corrosion resistance of a plating layer that contains a high concentration of Ca.

[0020] Therefore, the present inventors have investigated elements that can exert the same effect as Ca, and have found that Si is effective. Specifically, they have found that Si forms Mg-Si intermetallic compounds, but the Mg-Si intermetallic compounds have a property of being less likely to accumulate at the interface between the plating layer and the base material than Ca-containing intermetallic compounds. In other words, by including Si in the plating layer, it is possible to exert almost the same effect as Ca, while allowing the formed Mg-Si intermetallic compounds to accumulate at the center of the plating layer in the thickness direction, thereby improving the workability more than before.

[0021] [Hot-dip galvanized steel] The hot-dip plated steel material according to this embodiment will be described in detail below. The hot-dip plated steel material of the present embodiment is a hot-dip plated steel material having a steel material and a plating layer disposed on a surface of the steel material, and the average chemical composition of the plating layer is, in mass%, Al: more than 10.0%, less than 60.0%, Mg: 4.0% or more, 15.0% or less, Si: 3.5% or more, 8.0% or less, and further comprising Sn: 0% or more, 0.7% or less, Sr: 0% or more, 1.50% or less, Bi: 0% or more, 0.3% or less, In: 0% or more, 0.3% or less, Ca: 0% or more, 0.6% or less, Y: 0% or more, 0.3% or less, La: 0% or more, 0.3% or less, Ce: 0% or more, 0.3% or less, Li: 0% or more, 0.3% or less, Ni: 0% or more, 1.0% or less, Cu: 0% or more, 1.0% or less, Ag: 0% or more, 0.25% or less, Sb: 0% or more, 0.25% or less, Pb: 0% or more, 0.25% or less, B: 0% or more, 0.5% or less, P: 0% or more, 0.5% or less, Ti: 0% or more, 0.25% or less, Co: 0% or more, 0.25% or less, V: 0% or more, 0.25% or less, Nb: 0% or more, 0.25% or less, Mn: 0% or more, 0.25% or less, Zr: 0% or more, 0.25% or less, W: 0% or more, 0.25% or less, Fe: 0% or more, 5.0% or less, The remaining parts contain Zn and impurities.

[0022] Furthermore, the plating layer in the hot-dip plated steel material of this embodiment contains an Mg2Si intermetallic compound, and in an element distribution profile obtained by qualitatively analyzing the plating layer from the surface toward the steel material by glow discharge optical emission spectrometry, when the thickness of the region from the surface of the plating layer to the depth position at which an Fe intensity equivalent to 5% of the maximum Fe intensity is detected is Tg, the average value of the qualitative analysis values ​​of Si from the surface of the plating layer to Tg / 3 is Si(surf), the average value of the qualitative analysis values ​​of Si in the range from Tg / 3 to 2Tg / 3 starting from the surface of the plating layer is Si(centre), and the average value of the qualitative analysis values ​​of Si in the range from 2Tg / 3 to Tg starting from the surface of the plating layer is Si(deep), the following formula (1) is satisfied.

[0023] Si(surf) <Si(deep)<Si(centre) …(1)

[0024] (Steel) First, the steel material (original sheet) to be plated will be described. The steel material is, for example, mainly a steel plate, but the size is not particularly limited. The steel plate may be any steel plate that can be applied to a normal hot-dip galvanizing process. Specifically, this applies to steel plates that can be applied to a process in which the steel plate is immersed in molten metal and solidified, such as a continuous hot-dip galvanizing line (CGL). The size of the steel plate that can be applied is, for example, a plate thickness of 10 mm or less and a plate width of 2000 mm or less, but the size of the steel plate is not limited to this.

[0025] The quality of the steel material is not particularly limited. Examples of applicable steel materials include various steel plates and materials such as general steel, Al-killed steel, extra-low carbon steel, high carbon steel, various high tensile steels, some high alloy steels (steels containing corrosion-resistant strengthening elements such as Ni and Cr), steel for bolts, and steel wire for bridge cables. More specifically, the steel material may be, for example, a hot-rolled steel sheet as defined in JIS G 3131 (2018), a cold-rolled steel sheet as defined in JIS G 3141 (2017), a rolled steel material for general structure corresponding to so-called SS material, a so-called general steel as defined in JIS G 3193 (2019), a pre-plated steel thinly plated with various metals as described in JIS H 8641 (2021), JIS G 3302 (2019), 3303 (2017), 3313 (2017), 3314 (2019), 3315 (2017), 3317 (2019), and 3321 (2019), a rolled steel material for building structure as described in JIS G 3136 (2012), an Al-killed steel as described in JIS G 3126 (2015), an extra-low carbon steel, a high carbon steel, a JIS G Various high-tensile steels and some high-alloy steels (steels containing corrosion-resistant strengthening elements such as Ni and Cr) described in 3113(2018), 3134(2018), and 3135(2018) are applicable.

[0026] (Plating layer) Next, the plating layer provided on the steel material will be described. The plating layer according to the present embodiment includes a Zn-Al-Mg alloy layer. The Zn-Al-Mg alloy layer contains a Zn phase, an Al phase, and an MgZn2 phase. The plating layer according to the present embodiment also contains an Mg2Si intermetallic compound. Furthermore, the plating layer according to the present embodiment may contain other intermetallic compounds.

[0027] When the Zn phase contains alloy elements such as Al and Mg, the corrosion resistance is improved. Therefore, in the case of a plating layer containing such a Zn phase, even if it is a thin film (for example, about half the thickness of a normal Zn plating layer), it can exhibit the same corrosion resistance as a normal Zn plating layer. Similarly, even if the plating layer of this embodiment is a thin film, it ensures corrosion resistance equal to or greater than that of a conventional Zn plating layer.

[0028] MgZn2 phase The plating layer according to the present embodiment contains an MgZn2 phase. When a certain amount of the MgZn2 phase is contained in the plating layer, the corrosion resistance in a water-wet environment can be further improved.

[0029] Zn phase (Al-Zn phase, Zn-Al phase) The Zn phase mainly exists as a ternary eutectic structure (Zn / Al / MgZn2 ternary eutectic structure). In addition, when the coating layer contains a large amount of Al, the Zn phase may dissolve in the Al phase when Al and Zn mix together in the solid state to form an Al-Zn phase. On the other hand, Al may dissolve in the Zn phase to form a Zn-Al phase (the Al concentration in the phase is up to about 20%). The phase composed of Zn and Al is extremely easy to work with.

[0030] Al phase The Al phase exists in the plating layer in the form of a mass of primary Al crystals. The Al phase dissolves various elements, particularly Zn, in the plating layer during the solidification process. Since the plating layer of this embodiment has a high Al content, the Al phase becomes supersaturated with elements such as Zn during the solidification process. The Al phase forms a dendrite structure that spreads in a tree-like shape in the plating layer during the solidification process, forming the skeleton of the plating layer. The Al phase is soft and highly workable, and therefore plays a role in hindering the growth of cracks that have occurred and reducing fatal defects in the plating layer.

[0031] Mg2Si intermetallic compound The plating layer according to the present embodiment contains Mg2Si intermetallic compounds. The Mg2Si intermetallic compounds are intermetallic compounds observed in the form of islands with clear boundaries in the solidification structure of the plating layer containing Si. It is believed that Zn, Al and other additive elements are not dissolved in the Mg2Si intermetallic compounds, or that even if they are dissolved, the amount is extremely small. The Mg2Si intermetallic compounds can be clearly distinguished from other phases in the plating layer by microscopic observation. The Mg2Si intermetallic compounds are formed in the plating layer by the inclusion of Si in the plating layer.

[0032] Intermetallic compounds formed in a plating layer generally have the effect of increasing corrosion resistance and hardness because individual atoms are bonded in a complex manner. However, when intermetallic compounds are formed in a continuous layer on the plating surface and interface, they may coagulate and peel off during bending, and may cause surface and / or interface peeling due to differences in corrosion rates during corrosion.

[0033] Here, Ca is known as an element effective in improving the corrosion resistance and hardness of the plating layer. However, as described above, Ca-containing intermetallic compounds are compounds that tend to form layers, and are particularly prone to accumulating at interfaces. This is because intermetallic compounds based on CaZn4 are likely to form when an excessive amount of Ca is contained in a Zn-Al-Mg-based plating layer. In contrast, it has been found that Si tends to improve the corrosion resistance and hardness of the plating layer in a manner similar to Ca, and that Mg2Si intermetallic compounds in particular tend to accumulate less at interfaces than Ca-containing intermetallic compounds. In addition, the more the intermetallic compound accumulates in the center of the plating layer, the less likely powdering occurs even under severe processing conditions. By incorporating the Mg2Si intermetallic compound in the plating layer so as to satisfy the various formulas described below, the hardness of the plating layer can be further increased, the corrosion resistance can be improved, and good processability can be ensured.

[0034] The presence of intermetallic compounds such as Mg2Si intermetallic compound can be confirmed by the GDS method (glow discharge optical emission spectroscopy).

[0035] Next, a method for analyzing components in the plating layer in the depth direction within the plating layer according to this embodiment will be described.

[0036] The component analysis method in the depth direction inside the plating layer may be performed by glow discharge optical emission spectrometry (GDS) using a glow discharge optical emission spectrometer. In this embodiment, a LECO Japan 850A is used as the glow discharge optical emission spectrometer, but the measurement device is not limited to this. When performing the analysis in the depth direction, it is preferable to perform the analysis while performing Ar sputtering, and the analysis conditions are argon pressure: 0.27 MPa, output power: 30 W, output voltage: 1000 V, and discharge area: within a circular area with a diameter of 4 mm.

[0037] Component analysis using GDS is performed from the surface of the plating layer in the depth direction toward the steel material until the Fe concentration reaches 100% (reaching the base steel). Therefore, the analysis range of depth direction analysis using GDS is from the surface of the plating layer to the Zn-Al-Mg plating layer, the Al-Fe alloy layer, and part of the steel material. After GDS analysis, the sputter depth of the cross section is measured using a Tokyo Seimitsu Co., Ltd. "surfcom130A". Component analysis using GDS provides an element distribution profile in the depth direction of the plating layer. The element distribution profile shows the distribution of the content of each element in the depth direction when the total amount of detected elements is taken as 100%.

[0038] In this embodiment, in the element distribution profile obtained by performing a qualitative analysis from the surface of the plating layer toward the steel material by GDS, if the thickness of the region from the surface of the plating layer to the depth position where an Fe intensity equivalent to 5% of the maximum Fe intensity is detected is Tg, the average value of the qualitative analysis value of Si from the surface of the plating layer to Tg / 3 is Si(surf), the average value of the qualitative analysis value of Si in the range from Tg / 3 to 2Tg / 3 starting from the surface of the plating layer is Si(centre), and the average value of the qualitative analysis value of Si in the range from 2Tg / 3 to Tg starting from the surface of the plating layer is Si(deep), the following formula (1) is satisfied. Note that Si(surf), Si(centre), and Si(deep) are obtained by performing a qualitative analysis by GDS 10 times and averaging the qualitative analysis values ​​in the obtained element distribution profile. The qualitative analyses are performed at positions on the surface of the plating layer that do not overlap with each other.

[0039] Si(surf) <Si(deep)<Si(centre) …(1)

[0040] By accumulating the Mg2Si intermetallic compound in the center of the thickness direction of the plating layer (specifically, the aforementioned region) so as to satisfy the above (1), the workability can be improved and powdering can be avoided even under severe processing conditions. In other words, by satisfying formula (1), the hardness and corrosion resistance of the plating layer can be increased, and as a result, a plated steel material that is hard and has good workability and corrosion resistance can be obtained. It is believed that the presence of an insulator such as the Mg2Si intermetallic compound in areas where the potential is likely to change significantly, such as the center of the plating layer in the thickness direction or the boundary between the plating layer and Fe, suppresses the promotion of corrosion and improves corrosion resistance.

[0041] The Mg2Si intermetallic compound has the effect of increasing corrosion resistance and hardness. On the other hand, if a large amount of Mg2Si intermetallic compound is formed on the surface and interface of the plating layer, the Mg2Si intermetallic compound may peel off during processing. In addition, due to the difference in corrosion rate, surface and / or interface peeling of the Mg2Si intermetallic compound may occur during corrosion, which may impair workability and corrosion resistance. The Mg2Si intermetallic compound formed on the surface of the plating layer has a greater effect on the deterioration of workability and corrosion resistance. Therefore, in this embodiment, Si(surf) is made smaller than Si(deep). That is, by making the amount of Si in the region from the surface of the plating layer to Tg / 3 smaller than the amount of Si in the range from 2Tg / 3 to Tg, peeling due to the Mg2Si intermetallic compound during processing and corrosion can be suppressed, and workability and corrosion resistance can be further improved.

[0042] In this embodiment, in the element distribution profile obtained by qualitatively analyzing the surface of the coating layer toward the steel material by the GDS method, the above formula (1) is satisfied in a region up to a depth position where an Fe intensity equivalent to 5% of the maximum Fe intensity is detected. This region is roughly the same as the region where the Zn-Al-Mg alloy layer exists.

[0043] FIG. 1 shows an example of the results of depth direction analysis by GDS for the plating layer according to this embodiment. The graph shown in FIG. 1 is an element distribution profile. In this embodiment, the region that defines the above formula (1) is from the surface of the plating layer to a position that is 5% of the maximum Fe intensity when analyzed in the depth direction from the surface of the plating layer. For example, in the case of the analysis results shown in FIG. 1, since the maximum Fe intensity is 53 V, the above formula (1) is defined in the region up to the position of 5% of the intensity, that is, the position where the Fe intensity is 2.7 V.

[0044] Next, the index of the Mg2Si intermetallic compound based on X-ray diffraction will be explained.

[0045] The plating layer of the present embodiment satisfies the following formula (2) when, in an X-ray diffraction pattern of the plating layer surface measured using Cu-Kα radiation under conditions of an X-ray output of 50 kV and 300 mA, the diffraction intensities of the Mg2Si intermetallic compound are I(26.19°) and I(44.6°) and the background intensity is I(12.5°).

[0046] {I(26.19°)+I(44.6°)} / {2×I(12.5°)}>2.0 …(2) In the formula (2), I(n°) is the X-ray diffraction intensity at a diffraction angle of n°, and n is the diffraction angle (2θ) shown in the formula (2).

[0047] FIG. 2 shows an example of an X-ray diffraction pattern of the plating layer according to this embodiment. As shown in FIG. 2, the peaks of the Mg2Si intermetallic compound appear near 26.19° and near 44.6°. That is, I(26.19°) and I(44.6°) in formula (2) represent the X-ray diffraction intensity of the Mg2Si intermetallic compound at the diffraction angles of 26.19° and 44.6°, respectively. In this embodiment, when the background intensity is I(12.5°), by satisfying the above formula (2), an intermetallic compound having excellent corrosion resistance and hardness is formed in the plating layer. As a result, it is possible to develop high hardness and corrosion resistance while maintaining the plastic deformability of the plating surface and interface.

[0048] The plating layer of this embodiment may include an interface alloy layer (Al-Fe-based interface alloy layer) containing Al and Fe. The average thickness of the Al-Fe-based interface alloy layer is less than 5 μm. The Al-Fe-based interface alloy layer is an interface alloy layer between the steel material and the Zn-Al-Mg-based alloy layer, and is in contact with the surface of the steel material. In other words, the plating layer of this embodiment may be a single-layer structure composed of a Zn-Al-Mg-based alloy layer, or may be a laminated structure including a Zn-Al-Mg-based alloy layer and an Al-Fe-based interface alloy layer.

[0049] The Al-Fe-based interface alloy layer does not have a large effect on corrosion resistance, but it does affect the adhesion of the plating layer during processing of the hot-dip plated steel material and the workability (presence or absence of cracks). In particular, the Al-Fe-based interface alloy layer may affect the powdering resistance, which indicates the degree of peeling of the plating layer during processing. Usually, the thinner the thickness of the Al-Fe-based interface alloy layer, the fewer the crack initiation points of the plating layer during processing, and the powdering resistance can be improved. For this reason, in hot-dip plated steel materials that may be subjected to high processing when used as members, etc., it is preferable that the thickness of the Al-Fe-based interface alloy layer is as thin as possible. Specifically, the thickness of the intermetallic compound constituting the Al-Fe-based interface alloy layer is less than 5 μm. This thickness is preferably 2 μm or less, more preferably 1 μm or less, and even more preferably 0.5 μm or less. It may be 0.3 μm or less. This can suppress the occurrence of cracks during processing and further improve the powdering resistance. Furthermore, the ratio of the thickness of the Al-Fe interfacial alloy layer to the thickness of the plating layer is on average less than 10%, and more preferably less than 5%.

[0050] The Al-Fe-based interface alloy layer is formed on the surface of the steel material, specifically, between the steel material and the Zn-Al-Mg-based alloy layer. The Al-Fe-based interface alloy layer is a layer in which the Al5Fe2 phase is the main phase in the structure. The Al-Fe-based interface alloy layer is formed by mutual atomic diffusion between the base steel (steel sheet) and the plating bath. When a continuous hot-dip plating method is used as the manufacturing method, the Al-Fe-based interface alloy layer is likely to be formed in the plating layer containing the Al element. In this embodiment, since the plating bath contains Al at a certain concentration or more, the Al5Fe2 phase is formed most frequently in the Al-Fe-based interface alloy layer. However, since atomic diffusion takes time, the Fe concentration in the Al-Fe-based interface alloy layer is not uniform, and the Fe concentration may be high in the part close to the base steel. Therefore, the Al-Fe-based interface alloy layer may partially contain small amounts of the AlFe phase, Al3Fe phase, Al5Fe2 phase, etc. In addition, since the plating bath also contains Zn at a certain concentration, the Al-Fe-based interface alloy layer may also contain a small amount of Zn.

[0051] In the plating layer according to the present embodiment, a part of Si may be incorporated into the Al-Fe-based interfacial alloy layer to form an Al-Fe-Si intermetallic compound phase. The Al-Fe-Si intermetallic compound phase identified is the AlFeSi phase. The isomers of the AlFeSi phase include α phase, β phase, q1 phase, q2 phase, etc. Therefore, these AlFeSi phases may be detected in the Al-Fe-based interfacial alloy layer. The Al-Fe-based interfacial alloy layer containing these AlFeSi phases is also referred to as an Al-Fe-Si alloy layer.

[0052] Next, the average chemical composition of the plating layer will be described. When the plating layer has a single-layer structure of a Zn-Al-Mg alloy layer, the average chemical composition of the entire plating layer is the average chemical composition of the Zn-Al-Mg alloy layer. When the plating layer has a multilayer structure composed of an Al-Fe interfacial alloy layer and a Zn-Al-Mg alloy layer, the average chemical composition of the entire plating layer is the average chemical composition of the Al-Fe interfacial alloy layer and the Zn-Al-Mg alloy layer combined.

[0053] In the plating layer of this embodiment, the thickness of the Al-Fe-based interfacial alloy layer is preferably 10% or less of the total thickness of the plating layer. When the thickness of the Al-Fe-based interfacial alloy layer is sufficiently small compared to the total thickness of the plating layer, the Fe concentration of the plating layer is often 5% or less.

[0054] Al: more than 10.0%, less than 60.0% Al is an element that mainly constitutes the plating layer. If the Al content is 10.0% or less, a sufficient amount of Zn-Al phase may not be secured. Therefore, the Al content is more than 10.0%. On the other hand, if the Al content exceeds 60.0%, the corrosion resistance may decrease. Therefore, the upper limit of the Al content is 60.0% or less. The lower limit of the Al content is preferably 15.0% or more. Moreover, the upper limit of the Al content is preferably 45.0% or less, more preferably 30.0% or less.

[0055] Mg: 4.0% or more, 15.0% or less Like Zn, Mg is an element constituting the main part of the plating layer. Mg is an important element for improving corrosion resistance in the plated steel sheet according to the present embodiment. If the Mg content in the plating layer is less than 4.0%, the effect of improving corrosion resistance is not clear compared to the case where Mg is not contained. Therefore, the Mg content is set to 4.0% or more. On the other hand, if Mg is added excessively to a Zn-Al-Mg plating bath, a rapid oxidation reaction occurs on the bath surface of the plating bath, and plating cannot be performed stably. Therefore, in order to perform stable plating and ensure good manufacturability, the Mg content in the plating layer is set to 15% or less.

[0056] Si: 3.5% or more, 8.0% or less Si combines with Mg to form an intermetallic compound having a composition of Mg2Si. Si also suppresses excessive Al-Fe reaction, thereby suppressing the formation of an Al-Fe-based interface alloy layer. If the Si content is less than 3.5%, the amount of Mg2Si produced will be small, the hardness of the plating layer will be low, and the corrosion resistance may also decrease. On the other hand, if the Si content exceeds 8.0%, the amount of Mg2Si produced in the plating layer will be too large, causing the plating layer to break brittle, and the plating layer will coagulate and peel off from the plating surface, causing a powdering phenomenon, which may result in a decrease in corrosion resistance. Therefore, the Si content is set to 3.5% or more and 8.0% or less.

[0057] Sr: 0% or more, 1.5% or less Sr forms covalent bonds with Zn, Al, Si, etc. to form intermetallic compounds with excellent corrosion resistance and hardness. On the other hand, if the Sr content exceeds 1.5%, an excessive amount of Sr-based intermetallic compounds is generated in the plating layer, making the entire plating layer hard. As a result, when the plated steel material is used for molding, the plating layer is easily destroyed, and peeling of the plating layer, such as powdering, may occur. Therefore, the Sr content is set to 0.03% or more and 1.5% or less.

[0058] Sn: 0% or more, 0.7% or less Bi: 0% or more, 0.3% or less In: 0% or more, 0.3% or less Each of the elements Sn, Bi, and In is an element that promotes the softening of the plating layer when contained in the plating layer. Since Sn, Bi, and In are elements that can be contained arbitrarily, the content of each is set to 0% or more. When Sn is contained, Mg9Sn5 tends to form in the plating layer. Bi forms Mg3Bi2, and In forms Mg3In, etc. These elements are softer than the MgZn2 phase and have good workability, and when contained in the plating layer, the improvement of workability can be clearly confirmed. In addition, these elements have a high anticorrosive effect because they show very base electrochemical properties. By containing at least one of Sn, Bi, and In within the above range, the effect of improving the corrosion resistance of the processed part can be obtained.

[0059] Ca: 0% or more, 0.6% or less, Ca is an element that contributes to improving the hardness and corrosion resistance of the plating layer. On the other hand, when a large amount of Ca is contained in the plating layer, an intermetallic compound is formed with Zn and / or Al in the plating layer. The Ca-containing intermetallic compounds thus formed tend to accumulate, particularly on the surface of the plating layer, and in some cases, the accumulated Ca-containing intermetallic compounds grow coarsely and the Ca-containing intermetallic compounds are connected in layers. In the case of a plating layer in which Ca-containing intermetallic compounds are connected in layers, the Ca-containing intermetallic compounds may undergo brittle fracture during forming, causing the plating layer to peel off from the surface of the plating layer, resulting in a decrease in workability. Therefore, the Ca content is set to 0.6% or less.

[0060] Y: 0% or more, 0.3% or less La: 0% or more, 0.3% or less Ce: 0% or more, 0.3% or less Li: 0% or more, 0.3% or less Ni: 0% or more, 1.0% or less Cu: 0% or more, 1.0% or less Ag: 0% or more, 0.25% or less Sb: 0% or more, 0.25% or less Pb: 0% or more, 0.25% or less B: 0% or more, 0.5% or less P: 0% or more, 0.5% or less Ti: 0% or more, 0.25% or less Co: 0% or more, 0.25% or less V: 0% or more, 0.25% or less Nb: 0% or more, 0.25% or less Mn: 0% or more, 0.25% or less Zr: 0% or more, 0.25% or less W: 0% or more, 0.25% or less Y, La, Ce, Li, Ni, Cu, Ag, Sb, Pb, B, P, Ti, Co, V, Nb, Mn, Zr, and W all form intermetallic compounds with Si, Zn, Al, etc. However, when the content of these elements is within the above range, they do not affect the initial corrosion of the plating layer. On the other hand, when these elements are contained in excess, a potential difference occurs in the plating layer, which may cause a lot of initial white rust, so when they are contained, it is better to keep them within the above range.

[0061] Fe: 0% or more, 5.0% or less Since the hot-dip plated steel material of this embodiment is manufactured by a continuous hot-dip plating method, Fe may diffuse from the plated base material to the plated layer during manufacturing. As described above, in this embodiment, the Al concentration of the plated layer is high, and an Al-Fe-based interface alloy layer may be formed, but its thickness is thin. As a result, Fe may be contained up to a maximum of 5.0% in the plated layer, but as long as the Fe concentration is limited to 5.0% or less, there is no effect on the frequency of cracks in the plated layer. Therefore, the Fe content is 0 to 5.0%. The Fe content may be more than 0%.

[0062] Remainder: Zn and impurities The balance preferably contains Zn. Since the hot-dip plated steel material of this embodiment is a Zn-based plated steel material having high versatility, the element constituting the main phase of the plated layer is Zn.

[0063] Impurities refer to components contained in raw materials or components mixed in during the manufacturing process, but not intentionally added. For example, trace amounts of components other than Fe may be mixed into the plating layer as impurities due to mutual atomic diffusion between the steel material (base steel) and the plating bath. In addition, since metals with 3N purity are usually used to manufacture plating alloys, the concentration of impurities may be approximately 0.03% or less in total.

[0064] To identify the average chemical composition of the plating layer, the plating layer is stripped and dissolved using an acid containing an inhibitor that suppresses corrosion of the base steel (steel material) to obtain an acid solution. The acid solution is filtered to remove the insoluble matter, and the resulting residue is liquefied by an alkali fusion treatment. The resulting acid solution and the solution obtained by the alkali fusion treatment are then measured using ICP atomic emission spectroscopy or ICP-MS to obtain the chemical composition. There are no particular restrictions on the type of acid, so long as it is an acid that can dissolve the plating layer. If the area and weight are measured before and after stripping, the plating adhesion amount (g / m 2 ) can also be obtained at the same time.

[0065] [Method of manufacturing hot-dip plated steel] Next, a method for producing the hot-dip plated steel material according to this embodiment will be described. The manufacturing method of the plated steel material according to this embodiment is not particularly limited. Therefore, as a method for forming the above-mentioned Si-containing plating layer, a simple method of plating by directly adding Si to a Zn-Al-Mg-based plating bath is considered. However, in this method, Mg2Si intermetallic compounds are likely to be formed on the surface and its vicinity, not in the center of the plating layer. Therefore, as an example of a suitable manufacturing method for producing the hot-dip plated steel material of this embodiment, a method of supplying Si to the plating layer from a Si-containing pre-plating layer provided on the plating base sheet will be described below. In this specification, such a method of forming a predetermined pre-plating layer on the plating base sheet in advance and then performing Zn-Al-Mg hot-dip plating in this order is called a "two-stage plating method".

[0066] First, an Al-Si pre-plating layer is formed in advance on a base sheet for plating such as a cold-rolled or hot-rolled steel sheet. The pre-plating method may be hot-dip plating, electroplating, displacement plating, vapor deposition, etc. Furthermore, these pre-plating layers may be heated and alloyed.

[0067] When pre-plating on the base sheet is performed by hot-dip plating, the pre-plating may be performed under conditions for forming a normal aluminum plating, for example, in an Al-8 to 10% Si bath, and there are no particular restrictions.

[0068] Next, the original sheet to be plated is heated to 450 to 600°C, preferably to a temperature approximately equal to the temperature of the plating bath described below. This heating may also serve as annealing of the original sheet (hereinafter, this heating may be referred to as pre-annealing). By heating the steel sheet before immersion in the plating bath described below, it is possible to reduce temperature fluctuations in the plating bath.

[0069] The heated original sheet on which the pre-plating layer has been formed is immersed in a Zn-Al-Mg plating bath adjusted to obtain the desired plating components, and then pulled out, whereby the pre-plating layer is incorporated into the Zn-Al-Mg alloy layer to form the final plating layer. The plating bath temperature is preferably 480 to 550°C.

[0070] In addition, in order to incorporate the pre-plating layer into the Zn-Al-Mg alloy layer and obtain a plating layer with a single-layer structure, it is preferable to ensure that the original sheet is immersed in the plating bath for a certain period of time or more. Specifically, the immersion time is preferably between 3 and 10 seconds. In order to sufficiently incorporate the pre-plating layer into the Zn-Al-Mg alloy layer, the immersion time is preferably 4 seconds or more. If the immersion time is excessively long, the alloy layer at the interface between the plating and the steel sheet may become thick, which may cause the plating to peel off. Therefore, the immersion time is preferably 8 seconds or less.

[0071] In this embodiment, it is preferable to control the temperature when the plated original sheet is pulled up. In other words, by controlling the cooling conditions appropriately after immersion, Si is contained in the plated layer, and the desired Mg2Si intermetallic compound can be formed.

[0072] Specifically, in order to sufficiently form the Mg2Si intermetallic compound, it is preferable to set the average cooling rate in the temperature range of 550 to 450°C to 25°C / sec or less. If the average cooling rate in the temperature range of 550 to 450°C exceeds 25°C / sec, Si may be uniformly dispersed in the thickness direction of the plating layer, and the desired plating layer may not be obtained.

[0073] Cooling conditions in a temperature range outside the range of 550 to 450° C. are not particularly limited since they do not affect the formation of intermetallic compounds.

[0074] In this way, by appropriately controlling the cooling conditions after the plated base sheet is pulled out of the bath, the formation of Mg2Si intermetallic compounds on the surface and interface of the plated layer can be further suppressed, and the Mg2Si intermetallic compounds can be appropriately dispersed near the center of the plated layer. As a result, high plating hardness, workability, and corrosion resistance can be achieved while maintaining the plastic deformability of the plated surface and interface.

[0075] In addition, when a steel sheet on which an Al-Si pre-plating layer is formed is used as a plating substrate, the Mg2Si intermetallic compounds can be more concentrated in the center and in the vicinity of the interface of the plating layer, rather than on the plating surface, and as a result, the desired plating layer of this embodiment can be formed.

[0076] Next, a method for evaluating the performance of hot-dip galvanized steel products will be described.

[0077] (Bending workability) The bending workability of the plated steel material of this embodiment can be evaluated by measuring the amount of powdering (amount of peeling) when the material is bent back after being bent at 0R to 5R-60 degrees in a V-shape.

[0078] Specifically, after forming the material with a 2R-60-degree V-shaped die press, it is further bent back into a flat plate using a flat die. After V-shaping, a 24 mm wide cellophane tape is pressed against the valley and then pulled away, and a 90 mm long section of the cellophane tape is visually inspected. The evaluation criteria are as follows:

[0079] <Evaluation criteria> A: No peeling occurred. B: Peeling occurred partially at points (less than 5% of the processed area). C: There are areas where peeling occurred in a line (less than 5 to 10% of the processed area). D: There are areas where peeling occurred in a line (less than 10 to 20% of the processed area). E: The peeled area is almost completely peeled off (20% or more of the processed area).

[0080] (Corrosion resistance) A 0.8mm thick flat test piece is prepared, and a salt spray combined cycle corrosion test (CCT, JASO-M609-91) is carried out to measure the area ratio of red rust that has developed. The number of cycles is 600. The evaluation criteria are as follows:

[0081] <Evaluation criteria> A: No red rust occurs. B: Red rust area ratio: less than 10%. C: Red rust area ratio: 10% or more but less than 20%. D: Red rust area ratio: 20% or more.

[0082] (Hardness) The hardness measured by the Vickers test (Vickers hardness) is used as an evaluation index for the scratch resistance of the plating layer. Specifically, the Vickers hardness of the plating layer surface is measured with a load of 10 gf. The Vickers hardness is measured at 10 points on a cross section including the thickness direction of the plating layer, and the average of these measurements is used.

[0083] After the plating layer is formed, various chemical conversion treatments and painting treatments may be carried out.

[0084] In the hot-dip plated steel material of this embodiment, a coating may be formed on the plating layer. The coating may be formed in one layer or in two or more layers. Examples of the type of coating directly on the plating layer include a chromate coating, a phosphate coating, and a chromate-free coating. These coatings can be formed by known methods such as chromate treatment, phosphate treatment, and chromate-free treatment.

[0085] Chromate treatment includes electrolytic chromate treatment, which forms a chromate film by electrolysis, reactive chromate treatment, which forms a film by utilizing a reaction with the material and then washes away excess treatment liquid, and coating chromate treatment, which applies a treatment liquid to the substrate and then dries it without rinsing with water to form a film. Any of these treatments may be used.

[0086] Examples of electrolytic chromate treatments include electrolytic chromate treatments using chromic acid, silica sol, resins (phosphoric acid, acrylic resins, vinyl ester resins, vinyl acetate acrylic emulsions, carboxylated styrene butadiene latexes, diisopropanolamine-modified epoxy resins, etc.), and hard silica.

[0087] Examples of the phosphate treatment include zinc phosphate treatment, zinc calcium phosphate treatment, and manganese phosphate treatment.

[0088] Chromate-free treatments are particularly suitable because they do not place a burden on the environment. Chromate-free treatments include electrolytic chromate-free treatments that form a chromate-free film by electrolysis, reactive chromate-free treatments that form a film by utilizing a reaction with the material and then wash away excess treatment liquid, and coating-type chromate-free treatments that apply a treatment liquid to the substrate and dry it without rinsing with water to form a film. Any of these treatments may be used.

[0089] Furthermore, one or more organic resin films may be provided on the film directly on the plating layer. The organic resin is not limited to a specific type, and examples thereof include polyester resin, polyurethane resin, epoxy resin, acrylic resin, polyolefin resin, and modified products of these resins. The modified product here refers to a resin obtained by reacting a reactive functional group contained in the structure of these resins with another compound (monomer, crosslinking agent, etc.) containing a functional group capable of reacting with the functional group in the structure.

[0090] As such an organic resin, one or more organic resins (unmodified) may be mixed and used, or one or more organic resins obtained by modifying at least one other organic resin in the presence of at least one organic resin may be mixed and used. In addition, any coloring pigment or rust-preventive pigment may be contained in the organic resin film. Aqueous resins that have been dissolved or dispersed in water may also be used. EXAMPLES

[0091] Next, an embodiment of the present invention will be described, but the conditions in the embodiment are merely an example of conditions adopted to confirm the feasibility and effects of the present invention, and the present invention is not limited to this example of conditions. Various conditions can be adopted in the present invention as long as they do not deviate from the gist of the present invention and achieve the object of the present invention.

[0092] First, a cold-rolled steel sheet (SPCC) measuring 100 mm x 200 mm and having a thickness of 0.8 mm was prepared as the base sheet for plating. First, an Al-Si pre-plating layer as shown in Tables 1A and 1B was formed on the surface of this cold-rolled steel sheet using an Al-Si-based plating bath (bath temperature: 650°C). Note that "two-stage plating" in the "manufacturing method" column in Tables 1A and 1B indicates that the above-mentioned two-stage plating method was applied. "Sendzimer" in Tables 1A and 1B indicates that a method was applied in which the surface of the cold-rolled steel sheet was reduction-annealed and plated without applying pre-plating.

[0093] An Al-Si pre-plating layer was formed on an original sheet for plating to produce a substrate for plating, and then the substrate for plating was heated at 400° C. in a H2 (25%)-N2 atmosphere for 0.5 to 3.0 minutes.

[0094] The pre-annealed plated substrate was subjected to hot-dip plating using a hot-dip plating simulator.

[0095] First, alloys having the plating bath components shown in Tables 1A and 1B were prepared by vacuum melting, and plating baths were prepared in a completely oxygen-free, nitrogen-substituted atmosphere (O2 concentration less than 5 ppm). The remainder of the plating bath components in Tables 1A and 1B was essentially Zn. Next, one point on the plated substrate (the back surface at the center of the evaluation surface) was spot-welded to a K-type thermocouple to determine the temperature history until the plating solidification was complete. The plated substrate was then heated to the specified temperature in an H2 (25%)-N2 atmosphere. The plating bath temperature was set as shown in Tables 1A and 1B, and the plated substrate was immersed in the plating bath at an immersion speed of 500 mm / sec for the immersion time shown in Tables 1A and 1B. The plated substrate was then pulled out of the plating bath at a speed of 500 mm / sec.

[0096] Immediately after pulling up, the average plating thickness Tp was adjusted to 40 μm using N2 wiping gas, and then the material was cooled in the temperature range of 550 to 450°C at the average cooling rate shown in Table 1 by spraying N2 gas at a controlled flow rate in an oxygen-free, nitrogen-substituted atmosphere.

[0097] The plated steel sheets were obtained by the above steps. The thicknesses (μm) of the plated layers shown in Tables 2A and 2B include the thicknesses of the interfacial alloy layers, and were measured from the cross sections of the plated layers using an electron microscope.

[0098] Next, evaluation samples were cut out from each type of plated steel sheet. Samples for GDS analysis and SEM observation were cut out at 30 mm square positions on the opposite side of the thermocouple position. Samples (100 x 50 mm) for evaluating various characteristics were taken from the center of the plated layer in the planar direction.

[0099] The cut samples were evaluated by bending tests, Vickers hardness measurements, and corrosion tests (SST). The Fe content of the plating layer is not shown in the table, but it was in the range of 0 to 5%.

[0100] The evaluation results, the composition of the plating layer, the GDS analysis results, the XRD measurement results, etc. are shown in Tables 2A and 2B. The remainder of the plating layer composition in Tables 2A and 2B is substantially Zn. Note that the underlines in each table indicate that the results are outside the scope of the present invention, that the manufacturing conditions are not preferable, or that the characteristic values ​​are not preferable.

[0101] In the case of Example No. 52, the immersion time of the plated substrate in the plating bath was short, so the pre-plating layer could not be sufficiently incorporated into the Zn-Al-Mg alloy layer, and as a result, a single-layer structure of the plating layer could not be obtained.

[0102] In the case of Example No. 53, the temperature of the plating bath was low, so the pre-plating layer could not be sufficiently incorporated into the Zn-Al-Mg alloy layer, and as a result, a single-layer plating layer could not be obtained.

[0103] In the case of No. 54, the plating substrate was immersed in the plating bath for a long time, which caused the reaction between the plating bath and the original plate (base steel sheet) to proceed excessively. Specifically, an interfacial alloy layer approximately 5 μm thick was observed in a cross-sectional view of the plating layer using an electron microscope. Furthermore, the results of the GDS analysis of No. 54 showed no accumulation of Si in the center of the plating layer thickness direction.

[0104] In the case of No. 55, the high temperature of the plating bath caused excessive alloying between the plating bath and the base steel sheet. Specifically, an interfacial alloy layer with an average thickness of about 5 μm was observed in a cross-sectional view of the plating layer using an electron microscope. Furthermore, the results of the GDS analysis of No. 55 showed no accumulation of Si in the center of the plating layer thickness direction.

[0105] [Table 1A]

[0106] [Table 1B]

[0107] [Table 2A]

[0108] [Table 2B] [Industrial Applicability]

[0109] According to the above-mentioned aspect of the present invention, a hot-dip plated steel material having excellent plating hardness, corrosion resistance, and workability can be obtained. Therefore, the hot-dip plated steel material obtained can be suitably applied to the fields of automobiles, building materials, and the like, and has high industrial applicability.

Claims

1. Steel and A plating layer disposed on a surface of the steel material; A hot-dip galvanized steel material having the following properties: The plating layer comprises, in mass %, Al: more than 10.0%, less than 60.0%, Mg: 4.0% or more, 15.0% or less, Si: 3.5% or more, 8.0% or less, and further comprising Sn: 0% or more, 0.7% or less, Sr: 0% or more, 1.5% or less, Bi: 0% or more, 0.3% or less, In: 0% or more, 0.3% or less, Ca: 0% or more, 0.6% or less, Y: 0% or more, 0.3% or less, La: 0% or more, 0.3% or less, Ce: 0% or more, 0.3% or less, Li: 0% or more, 0.3% or less, Ni: 0% or more, 1.0% or less, Cu: 0% or more, 1.0% or less, Ag: 0% or more, 0.25% or less, Sb: 0% or more, 0.25% or less, Pb: 0% or more, 0.25% or less, B: 0% or more, 0.5% or less, P: 0% or more, 0.5% or less, Ti: 0% or more, 0.25% or less, Co: 0% or more, 0.25% or less, V: 0% or more, 0.25% or less, Nb: 0% or more, 0.25% or less, Mn: 0% or more, 0.25% or less, Zr: 0% or more, 0.25% or less, W: 0% or more, 0.25% or less, Fe: 0% or more, 5.0% or less, The balance has a chemical composition including Zn and impurities, The plating layer is made of Mg 2 Contains a Si intermetallic compound, A hot-dip plated steel material that satisfies the following formula (1): in an element distribution profile obtained by qualitatively analyzing a region from the surface of the plating layer toward the steel material by glow discharge optical emission spectrometry, Tg is the thickness of a region from the surface of the plating layer to a depth position at which an Fe intensity equivalent to 5% of the maximum intensity of Fe is detected, Si(surf) is the average value of the qualitative analysis values ​​of Si from the surface of the plating layer to Tg / 3, Si(centre) is the average value of the qualitative analysis values ​​of Si in the range from Tg / 3 to 2Tg / 3 starting from the surface of the plating layer, and Si(deep) is the average value of the qualitative analysis values ​​of Si in the range from 2Tg / 3 to Tg starting from the surface of the plating layer. Si(surf)<Si(deep)<Si(centre)…(1)

2. The hot-dip plated steel material according to claim 1, wherein an X-ray diffraction pattern of a surface of the plating layer measured using Cu-Kα rays under conditions of an X-ray output of 50 kV and 300 mA satisfies the following formula (2): {I(26.19°)+I(44.6°)} / {2×I(12.5°)}>2.0...(2) In equation (2), I(n°) is the X-ray diffraction intensity at a diffraction angle of n°, where n is the diffraction angle (2θ) shown in equation (2).

Citation Information

Patent Citations

  • MOLTEN Al-Zn-Mg-Si PLATED SHEET STEEL AND PRODUCTION METHOD THEREOF

    JP2016166414A

  • Highly corrosion-resistant plated steel sheet with excellent resistance to weld liquor embrittlement and coating adhesion

    JP2022501508A

  • HOT-DIP Al-Zn-Si-Mg-PLATED STEEL SHEET, SURFACE-TREATED STEEL SHEET, AND COATED STEEL SHEET

    WO2022091849A1

  • Plated steel

    WO2018139619A1

  • Zn-Al-Mg-BASED HOT-DIP PLATED STEEL SHEET AND METHOD FOR PRODUCING SAME

    WO2019230894A1